NEW DATA REGARDING THE GROUND WATER LEVEL CHANGES AT THE AMYNTAIO BASIN- FLORINA PREFECTURE, GREECE - Tzampoglou, P.; Loupasakis, C. (Bulletin of the Geological Society of Greece, 2016)
The site investigated is the Amyntaio basin where a productive semi-confined aquifer is developed at the quaternary deposits. In the present study, the piezometric curves which have been extracted before the beginning of the mine activity (1992), were compared with the recent ones (2015), aiming to study their diachronic changes. From the subtraction of the two aforementioned piezometric surfaces, a significant ground water drawdown that reaches 70 m near the mine was observed. This drawdown, during the last decades, proves that the aquifer has been overexploited by both the mine of PPC -to protect the slopes and to prevent the water outflow in the mine- and the wells for irrigation purposes. The level drop extends, on the west, to the villages of Valtonera and Anargyroi and the underground water flow directs towards the mine. The Amyntaio mine can be described as a well with a diameter up to a few kilometers. The interaction of the groundwater level drawdown with the intense fragmentation and the geotechnical characteristics of the geological formations of the region triggered extensive land subsidence phenomena damaging numerous villages, infrastructures and extensive farmlands.